A gold nanoparticle chemically modified gold electrode for the determination of surfactants. Issue 108 (8th November 2016) - Merli, Daniele; Ferrari, Chiara; Cabrini, Elisa; Dacarro, Giacomo; Pallavicini, Piersandro; Profumo, Antonella
Abstract : A gold nanoparticles modified gold electrode was developed for the determination of surfactants in solution, using a redox probe and exploiting the tendency of surfactants to adsorb onto the nanoparticles' surface. Abstract : A chemically modified electrode (CME) bearing gold nanoparticles assembled onto a gold electrode via a 1, 4-benzenedimethanethiol SAM bridge has been successfully employed for the determination of surfactants in solution, using a redox probe and exploiting the tendency of surfactants to be adhere to the high-energy nanoparticles' surface.